THE RELIABILITY, MINIMAL DETECTABLE CHANGE AND CONSTRUCT VALIDITY OF A CLINICAL MEASUREMENT FOR QUANTIFYING POSTERIOR SHOULDER TIGHTNESS IN THE POST‐OPERATIVE POPULATION - Salamh, Paul A. (Sports Physical Therapy Section, 2012)
BACKGROUND: Posterior shoulder tightness (PST) has been implicated in the etiology of numerous shoulder disorders. Although reliable and valid measures have been described for the non‐operative population one does not exist for the post‐operative population. STUDY DESIGN: Blinded repeated measures design. PURPOSE: Investigate the intrarater reliability, minimal detectable change at the 90% confidence interval (MDC(90)) and construct validity of an inclinometric measurement designed to quantify PST in the post‐operative population. METHODS: One investigator performed PST measurements on the operative shoulder of 23 participants. Passive internal and external rotation measurements were performed for the validity component of the investigation. RESULTS: Intrarater reliability using an intraclass correlation coefficient (ICC) model 3,k was good (ICC = 0.79). The MDC(90) indicated that a change of greater than or equal to 8 degrees would be required to be 90% certain that a change in the measurement would not be the result of inter‐trial variability or measurement error. Construct validity was supported by a statistically significant relationship between PST and internal rotation r = 0.54 and by a relationship between PST and external rotation r = 0.30 which was not statistically significant. CONCLUSION: The sidelying procedure described in this investigation appears to be a reliable and valid means for quantifying PST in the post‐operative population. Moreover, the use of inclinometry provides an absolute angle of tightness that may be used for intersubject comparison, documenting change, and to determine reference values. LEVEL OF EVIDENCE: Therapy, level 2b